2014
DOI: 10.1016/j.rbmo.2014.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of intrauterine insemination in patients with moderate-to-severe endometriosis

Abstract: Performing intrauterine insemination (IUI) in moderate-to-severe endometriosis patients is not implemented in international guidelines, as only limited data exist on treatment efficacy and safety. This retrospective study examined the efficacy and safety of two IUI treatment strategies performed between January 2007 and July 2012 in moderate-to-severe endometriosis patients. Eight (40.0%) versus seven (15.6%) ongoing pregnancies were accomplished in patients undergoing IUI with ovarian stimulation (n=20, 61 cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 28 publications
4
17
0
1
Order By: Relevance
“…In our experience, post-operative ovarian stimulation was associated with an increased pregnancy rate after laparoscopic diagnosis and treatment for superficial peritoneal endometriosis related infertility. Our findings were in line with previous studies [20][21][22][23][24][25][26][27] and inconsistent with others [28,29]. However, available data have shown major heterogeneities.…”
Section: Main Findingssupporting
confidence: 72%
See 1 more Smart Citation
“…In our experience, post-operative ovarian stimulation was associated with an increased pregnancy rate after laparoscopic diagnosis and treatment for superficial peritoneal endometriosis related infertility. Our findings were in line with previous studies [20][21][22][23][24][25][26][27] and inconsistent with others [28,29]. However, available data have shown major heterogeneities.…”
Section: Main Findingssupporting
confidence: 72%
“…Considering moderate to severe endometriosis associated infertility, operative laparoscopy could be considered to increase spontaneous pregnancy rate [34], but clear data on post-operative management were missing. Therefore the benefit of superovulation and IUI in moderate to severe endometriosis remains unclear [20].…”
Section: Main Findingsmentioning
confidence: 99%
“…It cannot be excluded that deep peritoneal lesions may progress under the influence of the higher levels of peripheral sex steroids that typically occur during ovarian hyperstimulation for IVF [147]. It is noteworthy that ureteral obstruction after IVF has been reported in two cases [148,149]. A precise estimation of the magnitude of this risk is lacking, but it is presumably extremely rare, and thus is not sufficient to claim a preventative role of surgery before IVF.…”
Section: Management Of Be In Patients Wishing To Conceivementioning
confidence: 99%
“…Our patients started directly with the IVF or ICSI cycle, contrary to the study of Van Der Houwen et al (2014b) [31], who showed that patients with rAFS stage III and IV endometriosis should have an intrauterine insemination (IUI) with ovarian stimulation before IVF with a maximum of 3 cycles because it is less expensive and less radical. Nevertheless, most of our patients did not have a patent Fallopian tube, but this was considered in our study because doing so did not waste a lot of time, especially because our cohort of patients was young.…”
Section: Discussionmentioning
confidence: 63%